2018
DOI: 10.3390/rs10020278
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Analysis of the Topographic Effects on Snow-Free Albedo over Rugged Terrain

Abstract: Topography complicates the modeling and retrieval of land surface albedo due to shadow effects and the redistribution of incident radiation. Neglecting topographic effects may lead to a significant bias when estimating land surface albedo over a single slope. However, for rugged terrain, a comprehensive and systematic investigation of topographic effects on land surface albedo is currently ongoing. Accurately estimating topographic effects on land surface albedo over a rugged terrain presents a challenge in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Although the multiscattering of the adjacent terrain can increase the outgoing radiations, multiscattering effects generally have little impact unless the land surface has high reflectance. This is in agreements with the model‐based analysis in Hao et al (), which showed that the more rugged the terrain, the more obvious topographic effects on the albedo and the albedo difference between the flat and rugged terrain could reach 0.28.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the multiscattering of the adjacent terrain can increase the outgoing radiations, multiscattering effects generally have little impact unless the land surface has high reflectance. This is in agreements with the model‐based analysis in Hao et al (), which showed that the more rugged the terrain, the more obvious topographic effects on the albedo and the albedo difference between the flat and rugged terrain could reach 0.28.…”
Section: Discussionsupporting
confidence: 92%
“…There is an urgent need to better understand the topographic effects on the land surface albedo to increase our knowledge of mountainous role in global climate change. Figures and reveal that the snow‐free MODIS albedo is highly sensitive to the topographic distribution, and thus, the topographic consideration is required in the surface albedo estimations even though the terrain is relatively gentle (10–20°), which is in line with previous studies (Cherubini et al, ; Hao et al, ; Wen et al, ). Figures 3–5 show that as the terrain becomes more and more rugged, MODIS albedo shows an overall decreasing trend, due to the stronger shadowing effects and the terrain obstruction for the hemispherical sky.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By recording the number of self-overlapped pixels of i as N ii (Ω), the inner multiple scattering is included by new inner view factors (F ii ). (10) Assume that the total incident light is defined as 1.0 with a diffuse fraction (k d ). The single scattering of i + and i − from diffuse light will be…”
Section: Estimation Of View Factors and Single Scatteringmentioning
confidence: 99%
“…Within a domain with a size larger than 0.5 km (hereafter named the km-scale), the land surface is more likely to be heterogeneous with changing elevations or mixed land covers. Especially in mountainous areas, forest BRDF and albedo are significantly affected by the heterogeneous terrain and complex vegetation composition [9,10]. To simulate the combined effects of heterogeneous terrain and complex vegetation composition on MODIS or MISR BRDF products, RT models are expected to contend with a domain (or scene) size greater than 0.5 km.…”
Section: Introductionmentioning
confidence: 99%